The Extent of Job Satisfaction among PNP Personnel at Gen. Trias Component City Police Station - Asido Jr, Zosimo; Bantiyag, Larry M.; Lacaste Jr., Hilario; Picardal, Jr, Teodoro M.; Postrero, Christopher M.; Villa, Elizabeth; Mobo, Froilan D.; Golla, Nathaniel S. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
The study sought to evaluate the level of job satisfaction among PNP personnel at the Gen. Trias Police Station, as assessed by the PNCOs and PCOs concerning Organizational Factors, Environmen-tal Factors, and Personal Factors. This study employed a quantita-tive-descriptive methodology. This research utilized a survey methodology for data collection. The research strategy employed stratified sampling to catego-rize a population into strata based on a known feature for each sampling unit, followed by the independent selection of samples from each stratum. The majority of respondents comprised forty-four (44) Police Non-Commissioned Officers and four (4) Police Commissioned Officers, indicating a predominance of male partic-ipation in this study. The study's ultimate outcome is a proposed action plan to im-prove job satisfaction among PNP personnel in Gen. Trias, Compo-nent City Police Station, as detailed in Sub-problem No. 4. The re-sults underscored the importance of organizational variables in-side the PNP organization. PNP personnel are influenced by their job environment and atmosphere. The data imply that sustaining open communication promotes greater outcomes.